Ecofeminist Issues in Helon Habila’s Novel Oil on Water - Michael, Ngusse; Daniel, Abiye (International Journal of Language and Literary Studies, 2022)
The purpose of this article is to examine ecofeminist issues in Helon Habila’s Oil on Water. Ecofeminism literary criticism was used to analyze the novel. Thus, based on the analysis made, the novel Oil on Water has various ecofeminist issues. Primarily, it mirrors the serious destruction of the natural environment in the Niger Delta. Because of this destruction, the ecosystem is in grave danger, and the annihilation of human and non-human beings is extensively portrayed in the novel. On the other hand, there is no clean environment including water in the Niger Delta due to oil spillage, no fresh air due to burning oil, and no peace due to the ongoing war. As a result, women, children, and indigenous peoples are forced to live in such a hostile environment. Furthermore, many living organisms become extinct as a result of oil companies’ contamination of the environment, which destroys their habitat. Rivers become contaminated, trees and vegetation dry up, fish and birds die, humans perish, and many people abandon their homes and are displaced on a regular basis. Finally, the novel depicts patriarchal dominance, environmental exploitation, and violations of indigenous peoples and women.